KARAKTERISTIK AGRONOMI BEBERAPA AKSESI DAN VARIETAS NILAM PADA UMUR PANEN BERBEDA - Muhamad Djazuli (Buletin Penelitian Tanaman Rempah dan Obat, 2011)
Agronomical Characteristics of Some Patchouli Accessions and Varieties at Several Harvest TimesInternal factor (genetic) and external fac-tor (ecological condition) strongly affect growth and productivity of patchouli. The objective of this study is to find out the agronomical characteristics of some ac-cessions, protoplast fusion, somaclones, and varieties of patchouli at 4, 5, 6 months after planting (MAP). For finding those agronomic characteristics, a pot ex-periment was conducted at Cimanggu Research Station, Bogor from May to De-cember 2009. The experiment was ar-ranged in randomized block design with 3 replicates. 12 accessions/varieties of pat-chouli consist of 4 somaclones, 4 acces-sions of protoplast fusion, 3 high yielding varieties, and 1 local variety were tested in this experiment. Growth and production components, number of oil gland and oil content of leaf were observed at 4, 5, and 6 MAP, while patchouli oil content were observed at 4 MAP. Results showed that protoplats fusion of PS 32 accession reveal the highest growth and biomass compo-nents compared to other accessions and varieties tested. Lower oil content of PS 32. The highest oil production per plant were found at PS 18 and PS 17. There is a linier correlation between oil content and number of oil gland in the leaf from 12 patchouli accessions and varieties tested. Patchouli alcohol content from the six pat-chouli accessions and varieties tested at 4 MAP were higher than 30%, being higher than minimal PA content for export. From those results it is indicated that even-though PS 18 and PS 17 accessions have high oil content, those accessions have some java patchouli genes characters, therefore evaluation of PS 18 and PS 17 to biotic and abiotic stress conditions are needed.